Creation of Business Identification Number in the Framework of UMKM Development in Temiyang Village, Kroya District, Indramayu Regency - Prety Nurfadilah; Rina Almaidah; Ade Setiawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
NIB is an abbreviation for Business Identification Number, which is an official identity issued by the Online Single Submission Institute. By having an NIB, business actors can easily apply for various permits, including Business Permits and Commercial or Operational Permits according to their respective business fields. In the implementation of making a Business Identification Number (NIB) based on UMKM data from Temiyang Village, there are several UMKM who still lack knowledge about understanding the mechanism and importance of making a Business Identification Number (NIB). Business actors in Temiyang Village are also very open and participate in supporting the implementation of NIB creation, especially since not many business actors understand digital technology, so with this program UMKM can be helped in the legality of their business. Based on the description of the problems that occur in businesses in Temiyang Village, the author is interested in helping business actors in Temiyang Village who do not yet have UMKM permits based on Government Regulation no. 24 of 2018 concerning Electronically Integrated Business Licensing Services. This program has a clear objective, namely so that UMKM in Temiyang Village have an NIB to develop their business, understand the importance of making an NIB, and know how to make permits through the OSS application. These clear objectives will provide guidance in designing and implementing the program effectively.